Study and Application of Cooling Technology for High Speed Motorized Spindle - CHENG Yao-nan; ZHANG Xian-peng; ZHANG Guang-xin; JIANG Wen-qi; LI Bao-wei (Journal of Harbin University of Science and Technology)
For the high-speed motorized spindle high-speed and structural integration of the temperature rise control and other technical problems, the existing cooling technology achievements of high-speed motorized spindles are systematically analyzed and summarized in depth. The thermal characteristics of high-speed motorized spindles are mainly analyzed in terms of the heat sources, heat transfer mechanisms, and internal heat generation effects. The cooling technology of the main components of the high-speed motorized spindle is explained. Based on passive cooling and active cooling, the methods, principles, advantages and disadvantages and applications of different cooling methods in the high-speed motorized spindle cooling technology are analyzed and reviewed from the aspects of motor, bearing and spindle. This paper explores the more cost-effective and efficient cooling technologies currently used in engineering practice to address potential challenges and predicts future trends in growth.